Distribution of Sicydium Valenciennes 1837 (Pisces: Gobiidae) in Mexico and Central America - Lyons, John (HIDROBIOLÓGICA, 2017)
Gobies of the genus Sicydium Valenciennes are widespread in Mexico and Central America, but have a different distribution pattern on the Atlantic and Pacific slopes of the region. On the Pacific slope, where mountain ranges are found near the coast and the coastal plain is narrow, Sicydium is continuously distributed in rivers from Mazatlán, Sinaloa, Mexico, to central Panama. On the Atlantic slope, Sicydium is known from to three disjunct areas where coastal mountain ranges are present, central Mexico, northern Honduras, and northeastern Costa Rica and northern Panama, and has not been recorded from intervening areas with broad coastal plains. The amphidromous life history of Sicydium gobies may prevent them from occupying rivers flowing through broad coastal plains. Sicydium gobies spawn in rocky mountainous river reaches and their larvae drift downstream to the ocean where they begin feeding. In rivers crossing broad coastal plains the distance to the ocean is relatively long, and I hypothesize that newly hatched larvae might starve before they reached their marine feeding habitat or that post-larvae might starve on their return migration up river to adult habitat.